Former à la notion de réseau par la conception et l’interprétation : l’atelier Reticulum - Florian Harmand; Arthur Perret (Humanités Numériques)
This paper describes the Reticulum workshop, a teaching experiment focused on the concept of network, involving students from two master’s courses (design and digital humanities). The workshop takes up the characteristics of the Reticulum conference cycle: interdisciplinary, interprofessional, intergenerational, intersecting knowledge and know-how. We present our approach as research-based teaching (with collaborative experimentation and knowledge production) and teaching-based research (with a study of conceptual pathways, technical choices and design mechanics). We analyse the workshop and its traces in order to show that the experiment is viable and reproducible; we examine the appropriation of the different techniques used during the workshop, and explain the underlying logics; finally, we describe the importance of modeling and visualising for reflective work, distinguishing between actual connectivity and interpretative connectivity.